Comparison of the Antioxidant Properties of Extracts Obtained from Walnut Husks as well as the Influence of Juglone on Their Evaluation - Małgorzata Olszowy-Tomczyk; Dorota Wianowska (Applied Sciences, 2024)
Concern for the future of the next generation leads to the search for alternative solutions for the proper management of materials considered as useless waste. This study fits into this research trend. Its aim is to demonstrate the potential of walnut husks as a source of compounds with antioxidant properties that can be used in non-food industries. Pressurized liquid extraction, i.e., one of the modern green extraction techniques used on an industrial scale, as well as conventional extraction in Soxhlet and maceration were applied to prepare the extracts. In order to assess in depth their antioxidant activity in relation to the content of characteristic components, various activity assessment methods were used in this research. The results proved that the husk components have such antioxidant properties that they can be of interest to the cosmetics and pharmaceutical industries regarding the management of this waste. The results confirmed the usefulness of assisted extraction in increasing the ecological and economic values of the proposed waste disposal. Moreover, they showed that juglonehas very weak antioxidant properties, and the antioxidant effect of the mixture containing husk extract and juglone solution is mainly additive.